Accelerates high temperature oxidation due to the change of Schottky’s Barrier Height of Cr2O3 layer in humid condition - Ani, Mohd Hanafi; Zaharudin, M. Z.; Anhar, Zaki; Musa, Mukhtaruddin; Abdul Hamid, Abd. Malek (IOP Publishing Ltd, 2020)
Development of the new generation of Ultra Supercritical (USC) power plant that has successfully achieved the targeted working temperature of 970 K. Nonetheless, increasing the operating temperature will further accelerate the high temperature oxidation of ferritic alloys of the boiler. Furthermore, water vapour in humid environment will make it easier for the alloy to further oxidize at high temperature. It is hypothesized that water vapour provides hydrogen that dissolves into the ferritic alloy susbstrate, hence altering their electronic state at the metal-semiconductor (oxide) interface. This study aims to measure Schottky Barrier Height (SBH) in dry and wet environment and relates it with acclerated oxidation behaviour. The Schottky Barrier was prepared by sputtering Cr2O3 onto the T91 boiler tube in high vacuum condition of 0.4 Pa, RF power 150W for an hour. The existance of Cr2O3 / Fe junction was confirmed by XRD analysis. The junction was then connected with platinum wire to act as the electrode for the current-voltage, I-V and capacitance-voltage, C-V test at high temperature. From the I-V graph, the reversed saturated current, Io was estimated and the SBH was calculated from the results. The SBH increased as the conductivity increased with the increment of temperature. From the C-V plots the value of Vbi was determined and used to calculate the SBH. The SBH increased with the increased of built in voltage. The result obtained from the two method agrees with one another. SBH value in wet condition is higher than that in dry condition. This is explained by the formation of space charge layer at metal/oxide interface due to dissolved hydrogen in metal, thus may change the transport property and accelerate the oxidation rate in water vapor.